2019
DOI: 10.1111/medu.13781
|View full text |Cite
|
Sign up to set email alerts
|

Is research on professional identity formation biased? Early insights from a scoping review and metasynthesis

Abstract: OBJECTIVE Despite a recent surge in literature identifying professional identity formation (PIF) as a key process in physician development, the empiric study of PIF in medicine remains in its infancy. To gain insight about PIF, the authors examined the medical literature and that of two other helping professions.METHODS The authors conducted a scoping review and qualitative metasynthesis of PIF in medicine, nursing and counselling/psychology. For the scoping review, four databases were searched using a combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
101
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 114 publications
(346 reference statements)
3
101
0
8
Order By: Relevance
“…Demographic information from the participants of this work concerning gender, age, race, ethnicity and sexual orientation were collected—recent work has demonstrated that models of professional identity formation often do not pay heed to participants’ sociocultural data, generating uncertainty as to whether much work into identity formation is applicable to those who do not identify as heterosexual white males 39…”
Section: Methodsmentioning
confidence: 99%
“…Demographic information from the participants of this work concerning gender, age, race, ethnicity and sexual orientation were collected—recent work has demonstrated that models of professional identity formation often do not pay heed to participants’ sociocultural data, generating uncertainty as to whether much work into identity formation is applicable to those who do not identify as heterosexual white males 39…”
Section: Methodsmentioning
confidence: 99%
“…In addition to demonstrating the patterns of bias that occur within communities of practice, this work demonstrates the influence of gendered experiences on students’ professional identity development, a previously underexplored area that Volpe et al argue has rendered much research regarding professional identity biased in favour of white men. 64 As paradigmatic trajectories within communities of practice ‘embody the history of the community through the very participation and identities of practitioners’, 50 they also embody the gender bias entrenched within healthcare services. Hence, as students draw on these trajectories to form their identities within communities, gender bias plays a key role.…”
Section: Discussionmentioning
confidence: 99%
“…Professional identity formation is a difficult journey for most, but there is emerging evidence that it may be particularly hard for some groups. Previous research has shown that professional identity may ‘fit’ less easily when students and practitioners are not members of the middle‐class White male hegemony . Indeed, our recent scoping review of PIF studies concluded: ‘… the experience of PIF is very likely to be extremely different, and perhaps more difficult, for members of under‐represented minorities, working class individuals, women and others who do not typify the White male medical culture.’…”
mentioning
confidence: 99%